Adverse effects of energy restriction on myogenic enzymes in judoists - Umeda, T.; Nakaji, S.; Shimoyama, T.; Yamamoto, Y.; Totsuka, M.; Sugawara, K. (Journal of Sports Sciences, 2004)
In this study, we examined the effects of weight reduction by restricting energy intake on muscle function and serum concentrations of myogenic enzymes in judoists. Twenty-seven male judoists aged 19.3 +/- 0.6 years (mean +/- s) were divided into three groups based on the extent of body weight reduction: high weight reduction (height 1.70 +/- 0.05 m, body mass 78.5 +/- 13.6 kg), low weight reduction (height 1.70 +/- 0.05 m, body mass 80.7 +/- 13.1 kg) and a group that maintained body weight while continuing to perform exercise training (height 1.78 +/- 0.07 m, body mass 78.7 +/- 8.8 kg). Body composition, blood biochemistry, energy intake and anaerobic power were assessed on four occasions: 20 days (baseline data), 4 days and 1 day before and 7 days after competition. Compared with baseline, body mass and fat-free mass were significantly lower 1 day before competition in the high and low weight reduction groups (both P < 0.01); these changes persisted for 7 days after competition in the high weight reduction group. Serum creatine kinase was significantly elevated 1 day before competition in all groups (all P < 0.05), and remained higher 7 days after competition in both the high and low weight reduction groups. Compared with baseline, maximal anaerobic power was significantly lower 1 day before competition only in the high weight reduction group (P < 0.01). Our results suggest that energy restriction in addition to intense exercise training before major competition has an adverse effect on anaerobic power and elevates serum creatine kinase concentration, leading to an impairment of muscular function and an increased susceptibility of muscle tissue to injury.